Backmatter (Publication Ethics, Copyright Transfer Agreement for Publishing Form) - Istadi, Istadi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
Backmatter (Publication Ethics, Copyright Transfer Agreement for Publishing Form)